Using Sports Participation as a Lifeline to Promote Psychological Wellbeing and Happiness among Older Individuals in China: Mediating Role of Social Capital Dimensions - Yuning Sun; Yaohui Lin, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
There is substantial evidence linked with the positive outcomes of sports-based activities on the health and well-being of individual which natural tends to deteriorate once they reach a certain age. From a positive aging view, the promotion of sports participation for improving the health, physical and mental, and wellbeing outcomes have been used as a key strategy. The present study considers this strategy and formulates a framework to evaluate the impacts imposed by sports participation on the general happiness and wellbeing of the older population. To better understand the role of sports participation among older adults, the role of social capital on the relationship between sport participation and happiness among the older population and the relationship between sport participation and well-being has also been considered. For this purpose, a convenience-based sample of 310 sports-participating older population is studied in China. The results show that sports participation predicts both well-being and general happiness in older individuals. Moreover, two of the sub-dimensions of the social capital, neighborhood connections, and feelings of trust and safety, are found to significantly mediate the associations. The study is novel from the standpoint that the context of the study is set in China and it produces new empirical findings as well. The main limitation of the study is that a convenience sample has been used and the scope is restricted to China. The study lends a number of important contributions to sports psychology and epidemiological perspectives.